(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2026)
The article explores the theoretical aspects of a systems approach to the quality management of products and services at trade and service enterprises. Modern scientific approaches to the formation of quality management systems are summarized, and the role of digital technologies in improving the efficiency of quality management is identified. Based on scientific research, the process of systemic quality management of products and services at trade and service enterprises is examined, and their development trends are analyzed. It is determined that the implementation of international standards, particularly ISO 9001, contributes to the formation of an effective quality management system and ensures a stable level of service quality. At the same time, the main challenges remain a formal approach to the implementation of quality systems and an insufficient level of process digitalization. The generalized quality model becomes particularly significant in the service sector, where quality largely depends on the human factor, speed of service, communication levels, and individual customer perception. For trade enterprises, it serves as an important tool for ensuring the stability of the assortment, service, logistics, and interaction with consumers. It is argued that a systems approach to the quality management of products and services is an effective tool for increasing the competitiveness of trade and service enterprises. A generalized model of systemic quality management is proposed, which takes into account the interconnection of business processes and customer orientation. Such a model allows for the integration of key components of quality management, ensures the coordination of all enterprise departments, improves resource efficiency, reduces costs, minimizes errors, and contributes to the formation of competitive advantages.